2020
DOI: 10.1590/1678-4162-10316
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass yield, and meat quality of broilers supplemented with organic or inorganic zinc

Abstract: A total of 640 one-day-old Cobb broiler chicks, half male and half female, were reared up to 49 days of age. A completely randomized 2 × 4 factorial design was used. Experimental treatments consisted of four levels of organic zinc supplementation and one control (inorganic zinc supplementation) and two levels of sex (female and male), with four replicates of 16 birds per experimental plot. Animal performance, carcass and cut yields, and meat quality were evaluated. Feed intake increased with zinc supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
4
0
0
Order By: Relevance
“…The results showed that dressed yield did not vary significantly among all groups ( p > 0.05). These observations were consistent with the findings of others 29 , 34 , 35 . There were no significant differences in the sum of breast and leg muscle yield between broilers fed LP diet with MHA-Zn (90 mg/kg) and those fed NP diet, indicating that addition of 90 mg/kg MHA-Zn to LP diet did not reduce the proportion of edible part of broilers despite a reduction in feed intake.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that dressed yield did not vary significantly among all groups ( p > 0.05). These observations were consistent with the findings of others 29 , 34 , 35 . There were no significant differences in the sum of breast and leg muscle yield between broilers fed LP diet with MHA-Zn (90 mg/kg) and those fed NP diet, indicating that addition of 90 mg/kg MHA-Zn to LP diet did not reduce the proportion of edible part of broilers despite a reduction in feed intake.…”
Section: Discussionsupporting
confidence: 94%
“…Except for the first two weeks, FCR in Group C (90 mg/kg MHA-Zn) was the closest to that in control group. This was consistent with the reports by Bueno et al 29 and Jahanian et al 30 , who also suggested that supplementation with organic zinc (zinc acetate dihydrate, Zn-lysine chelate and MHA-Zn) significantly improved intake of feed and feed efficiency of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…The body weight of broilers in this group was statistically signi cantly higher than in the other two LP groups, and FCR was the closest to the control group. This coincides with the reports by Bueno and Jahanian et al, who also suggested that the supplementation of organic zinc (zinc acetate dihydrate, Zn-lysine chelate and MHA-Zn) signi cantly improves the intake of feed and feed e ciency of broilers 23,24 .…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the breast and leg muscle yield (edible part) of poultry is the most important part of meat performance. The results showed that the percentage of dressed yield did not signi cantly vary among all groups (P > 0.05), these observations were in conformity with the ndings of others 24,27,28 . There were no signi cant differences in the percentage of sum of breast and leg muscle yield fed with MHA-Zn (90 mg/kg) in the LP diet compared to the NP diet group, indicating that the addition of 90 mg/kg MHA-Zn in the LP diet did not reduce the proportion of edible part of broilers while reducing feed intake.…”
Section: Discussionsupporting
confidence: 86%